Promoting Elementary Students’ Outcome in Social Science With PAIKEM Approach - Lazim N; Hendri Marhadi; Emelda Rahmi (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2018)
This study aims to examine the influence PAIKEM approach to promote primary students’ learning outcomes in social science. The method of this study is a quasi experiment and conducted by 30 students 3rd graders in elementary school. The results of this study primary students' learning outcomes after implementingpaikem approach, the average score of student learning outcomes in the initial data is worth 63.67 while the first cycle is worth 70.67 and the average students’ learning outcomes in the second cycle is worth 80.33. From the initial data to the first cycle increased by 7 points (10.99%) and from the beginning to the second cycle increased by an increase of 16.66 points (26.17%). To be concluded, implementing PAIKEMapproach could effectively promote primary students’ learning outcome in social science.